Mindfulness for life - Kuyken, Willem (New York, NY The Guilford Press, 2024)
"Mindfulness is exceptionally easy to get started with, and people often experience benefits almost immediately. Why, then, do many initial enthusiasts end up dropping the practice after a short while? According to Oxford professor and leading mindfulness expert Willem Kuyken, it's because traditional mindfulness training is too far removed from how we actually live. This next-generation resource brings mindfulness home by teaching core skills in easy-to-integrate ways that touch directly on life's daily challenges. Dr. Kuyken provides stepping stones for building a personal practice that is sustainable, purposeful, and richly rewarding, now and for years to come. Interweaving ancient wisdom and modern scientific psychology, the book presents stories, quotations, reflection questions, tips for overcoming hurdles, and compelling guided practices, including audio tracks at the companion website. Key Words/Subject Areas: meditations, guided practices, audio downloads, mindfulness, Buddhist psychology, cognitive-behavioral therapy, self-compassion, training programs, manuals, Buddhism, self-soothing, exercises, workbooks, body scan, self-help, classes, learning, programs, how to do Audience: Anyone seeking support to build mindfulness into their life in truly meaningful and sustainable ways"-- Provided by publisher
Introduction. A Life Well Lived: Beginning with the End in Mind -- Wake Up! -- Pay Attention! -- Coming Home to Our Bodies -- Appreciating the
Life We Have -- Our Most Important Natural Resource: Our "Body--Mind" -- How We React to Stress and Difficulties -- Befriending Our Minds --
Perspective: Changing the View -- Responding Wisely -- Cool Head and Warm Heart: The Art of Balance and Equanimity -- Living Well: Taking
Care of Ourselves, Our Relationships, and the World -- A Life Well Lived
Includes bibliographical references and index.
Keywords: Mindfulness (Psychology).; Meditation -- Therapeutic use; PSYCHOLOGY / Mental Health; SOCIAL SCIENCE / Social Work